Synthesis and characterisation of copper oxide doped zinc oxide nanophotocatalyst and its photocatalytic ability in methyl orange dye degradation - Razali, Norzafirah (2011)
CuO-doped ZnO (CuO-ZnO) nanophotocatalyst was synthesized by stirring CuO and ZnO in absolute methanol solution overnight, at ambient pressure and temperature. CuO was initially produced from four different precursors namely copper acetate, copper sulphate, copper chloride, and copper nitrate while the precursor of ZnO was produced from zinc acetate. Effects of different precursors to the properties of CuO (CA, CS, CCl, CN) were investigated. Next, the produced CuOs were doped onto ZnO (CZA, CZS, CZCl, CZN) and the properties were studied. Thermogravimetry analysis (TGA), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-Ray Fluorescence (XRF), Atomic Absorption Spectroscopy (AAS), surface area and pore distribution (BET and BJH), and Zeta potential were used to characterize the synthesized ZnO, CuO and CuO-ZnO nanophotocatalysts. In photocatalysis, the ability of ZnO, CuO and CuO-ZnO nanophotocatalysts in decolorizing methyl orange (MO) dye were evaluated using UV-Vis spectroscopy while the degradation process was determined through Total Organic Carbon (TOC) analysis. Interaction between intermediates and by-products during the synthesis process of CuO affected the crystallinity, morphology and particle size of synthesized CuOs. Although no significant changes in most of the physical properties of ZnO was observed, the introduction of CuO had improved the photoactivity of ZnO. This attributed to the enhancement in surface area of the CuO-ZnO photocatalyst and the ability of CuO to act as electron acceptor that prolongs charge separation which resulted in a better photodegradation process. Among the prepared CuO-ZnO nanophotocatalysts, CZN (CuO produced from copper nitrate) exhibited the highest rate of methyl orange photodegradation. In order to determine the optimum % of CuO to be doped on ZnO, 0.5 – 2.0 % CuO-ZnO photocatalyst were synthesized using CZN. No significant changes in the properties of ZnO as the % of CuO doped were varied. In photodegrading MO, 1.0% of CuO-ZnO nanophotocatalyst showed the highest degradation rate. The optimum condition in degradation of MO was obtained at dye concentration of 30 ppm and pH of 7 by using 1.5g of 1.0% of CuO-ZnO photocatalyst. The photoactivity of CuO-ZnO was maintained until fifth cycle in the study of reusability. 1.0% of CuO had significantly improved the photoactivity of bare ZnO under visible-light irradiation. The potential of 1.0% CuO-ZnO nanophotocatalyst in degrading real dye-containing industrial wastewater from one of textile factories at Melaka was evaluated. From the TOC analysis, 22% of total organic carbon in the real wastewater was degraded within 60 min.